Mediating mysteries, understanding liturgies: on bridging the gap between liturgy and systematic theology - Geldhof, Joris (Ephemerides theologicae Lovanienses / Bibliotheca, 2015)
"The starting point for the present volume is the conviction that the liturgy contains, transmits, and partakes in the central mysteries of the Christian faith.... This book ... aims at contributing to the ongoing discussions about the ways in which the mysteries of faith are mediated and how Christian liturgies can or must be understood."--Introduction